2020
DOI: 10.3389/fncel.2020.00276
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Is Involved in the Maintenance of Cerebral Pericytes

Abstract: Pericytes play a central role in regulating the structure and function of capillaries in the brain. However, molecular mechanisms that drive pericyte proliferation and differentiation are unclear. In our study, we immunostained NACHT, LRR and PYD domainscontaining protein 3 (NLRP3)-deficient and wild-type littermate mice and observed that NLRP3 deficiency reduced platelet-derived growth factor receptor β (PDGFRβ)-positive pericytes and collagen type IV immunoreactive vasculature in the brain. In Western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…In the 8‐day treatment experiment, withdrawal of IL‐1β for the last 3 days restored expression of LRP1 in cultured pericytes (Figure 6j,k; two‐way ANOVA, p <.05). The short‐term treatment of IL‐1β markedly increased expression of PDGFRβ and CD13, which corroborates our recent finding (Quan et al, 2020) (Figure 6f,h,i; one‐way ANOVA, p <.05). The long‐term treatment of IL‐1β only at a high concentration (e.g., 50 ng/ml) tended to decrease the expression of PDGFRβ and CD13; however, it was not statistically significant (shown in Figure 6l,m with solid lines; one‐way ANOVA, p >.05).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In the 8‐day treatment experiment, withdrawal of IL‐1β for the last 3 days restored expression of LRP1 in cultured pericytes (Figure 6j,k; two‐way ANOVA, p <.05). The short‐term treatment of IL‐1β markedly increased expression of PDGFRβ and CD13, which corroborates our recent finding (Quan et al, 2020) (Figure 6f,h,i; one‐way ANOVA, p <.05). The long‐term treatment of IL‐1β only at a high concentration (e.g., 50 ng/ml) tended to decrease the expression of PDGFRβ and CD13; however, it was not statistically significant (shown in Figure 6l,m with solid lines; one‐way ANOVA, p >.05).…”
Section: Resultssupporting
confidence: 92%
“…To quantify vasculature in the brain, our established protocol was used (Decker et al, 2018; Quan et al, 2020). Four serial paraffin‐embedded sections per mouse with 300 μm of distance in between were deparaffinized, heated at 80°C in citrate buffer (10 mM, pH = 6) for 1 hr and digested with Digest‐All 3 (Pepsin) (Thermo Fisher Scientific) for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings also underline the importance of establishing a reliable and consistent method to implement lectin use in histological staining of blood vessels. Indeed, several recently published studies relied on the IB4 lectin to stain blood vessels in embryos [ 46 ], in the retina [ 47 , 48 , 49 ], and also in the brain [ 50 , 51 ]; however, our systematic comparison showed that the LEA lectin is preferable to IB4 in such applications, particularly in the brain of adult mice.…”
Section: Discussionmentioning
confidence: 97%
“…Western blotting analysis was performed as described [17]. Briefly, Frozen mouse lung tissue or NSCLC cells were homogenized on ice in 5 × radioimmunoprecipitation assay buffer (RIPA buffer; 50 mM Tris [pH 8.0], 150 mM NaCl, 0.1% SDS, 0.5% sodiumdeoxy-cholate, 1% NP-40, and 5 mM EDTA) supplemented with protease inhibitor cocktail (Sigma-Aldrich, St.Louis, MO, USA), followed by centrifugation at 16,000 × g for 30 minutes at 4 °C to collect the supernatants.…”
Section: Western Blotting Analysismentioning
confidence: 99%